Galaxy source counts at 7.7, 10, and 15 μm with the James Webb Space Telescope. Issue 1 (24th September 2022) - Ling, Chih-Teng; Kim, Seong Jin; Wu, Cossas K-W; Goto, Tomotsugu; Kilerci, Ece; Hashimoto, Tetsuya; Lin, Yu-Wei; Wang, Po-Ya; Ho, Simon C-C; Hsiao, Tiger Yu-Yang
ABSTRACT: We present mid-infrared (IR) galaxy number counts based on the Early Release Observations obtained by the James Webb Space Telescope ( JWST ) at 7.7-, 10-, and 15-μm (F770W, F1000W, and F1500W, respectively) bands of the Mid-Infrared Instrument (MIRI). Due to the superior sensitivity of JWST, the 80-per cent completeness limits reach 0.32, 0.79, and 2.0 μJy in F770W, F1000W, and F1500W filters, respectively, i.e. ∼100 times deeper than previous space IR telescopes such as Spitzer or AKARI . The number counts reach much deeper than the broad bump around 0.05∼0.5 mJy due to polycyclic aromatic hydrocarbon (PAH) emissions. An extrapolation towards fainter flux from the evolutionary models in the literature agrees amazingly well with the new data, where the extrapolated faint-end of IR luminosity functions combined with the cosmic star-formation history to higher redshifts can reproduce the deeper number counts by JWST . Our understanding of the faint IR sources has been confirmed by the observed data due to the superb sensitivity of JWST .